Microglial phagocytosis of living photoreceptors contributes to inherited retinal degeneration. Issue 9 (2nd July 2015) - Zhao, Lian; Zabel, Matthew K; Wang, Xu; Ma, Wenxin; Shah, Parth; Fariss, Robert N; Qian, Haohua; Parkhurst, Christopher N; Gan, Wen‐Biao; Wong, Wai T
Abstract Retinitis pigmentosa, caused predominantly by mutations in photoreceptor genes, currently lacks comprehensive treatment. We discover that retinal microglia contribute non‐cell autonomously to rod photoreceptor degeneration by primary phagocytosis of living rods. Using rd10 mice, we found that the initiation of rod degeneration is accompanied by early infiltration of microglia, upregulation of phagocytic molecules in microglia, and presentation of "eat‐me" signals on mutated rods. On live‐cell imaging, infiltrating microglia interact dynamically with photoreceptors via motile processes and engage in rapid phagocytic engulfment of non‐apoptotic rods. Microglial contribution to rod demise is evidenced by morphological and functional amelioration of photoreceptor degeneration following genetic ablation of retinal microglia. Molecular inhibition of microglial phagocytosis using the vitronectin receptor antagonist cRGD also improved morphological and functional parameters of degeneration. Our findings highlight primary microglial phagocytosis as a contributing mechanism underlying cell death in retinitis pigmentosa and implicate microglia as a potential cellular target for therapy.